1971
DOI: 10.1073/pnas.68.9.2227
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Release of Dopamine-β-Hydroxylase from Sympathetic Nerves by Calcium and Phenoxybenzamine and Its Reversal by Prostaglandins

Abstract: Dopamine-j8-hydroxylase (EC 1.14.2.1), an enzyme localized in sympathetic synaptic vesicles, was released together with norepinephrine during in vitro stimulation of the hypogastric nerve that innervates the vas deferens of the guinea pig. Stimulation of the nerve in the presence of high concentrations of calcium (7.5 mM) or phenoxybenzamine caused a marked increase in the amounts of the enzyme and norepinephrine released into the bath. The augmentation of release of dopamine-,0-hydroxylase by 7.5 mM calcium o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

1972
1972
2002
2002

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…The activity of the autonomic nervous system increased during TXAPT-C: thyroidectomized and autografted parathyroid control rats; TXAPT-D: thyroidectomized and autografted parathyroid DOCA-treated rats; TXPTX-C: thyroparathyroidectomized control rats; TXPTX-D: thyroparathyroidectomized DOCA-treated rats; TXPTX-CT4; thyroparathyroidectomized control rats treated with L-thyroxine alone; TXPTX-DT4; thyroparathyroidectomized rats DOCA-treated rats given a thyroxine supple- Reid et al (1975) have reported increased serum catecholamines in DOCA-treated rats. Hypocalcemia after parathyroid removal probably diminished noradrenaline release from sympathetic nerves, since variations in calcium concentration produced this phenomenon (Johnson, Thoa, Weinshilboum, Axelrod & Kopin, 1971;George & Leach, 1975). Parathyroidectomy may protect against development of hypertension by partially inactivating the autonomic nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of the autonomic nervous system increased during TXAPT-C: thyroidectomized and autografted parathyroid control rats; TXAPT-D: thyroidectomized and autografted parathyroid DOCA-treated rats; TXPTX-C: thyroparathyroidectomized control rats; TXPTX-D: thyroparathyroidectomized DOCA-treated rats; TXPTX-CT4; thyroparathyroidectomized control rats treated with L-thyroxine alone; TXPTX-DT4; thyroparathyroidectomized rats DOCA-treated rats given a thyroxine supple- Reid et al (1975) have reported increased serum catecholamines in DOCA-treated rats. Hypocalcemia after parathyroid removal probably diminished noradrenaline release from sympathetic nerves, since variations in calcium concentration produced this phenomenon (Johnson, Thoa, Weinshilboum, Axelrod & Kopin, 1971;George & Leach, 1975). Parathyroidectomy may protect against development of hypertension by partially inactivating the autonomic nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Both electron microscopic (13)(14)(15) and biochemical evidence (9,11,12) indicate that the adrenergic nerve discharges the neurotransmitter by a process of exocytosis. Exocytosis presunmably involves a fusion of norel)in el)phrine storage-vesicle membrane with the neuronal membrane, followed by an extrusion of both the neurotransmitter and the soluble contents of the vesicles, including the high-molecular-weight protein (300,000), dopaminie-f-hydroxylase.…”
Section: )1 Scu Ssionmentioning
confidence: 99%
“…Observation of release of norepinephrine and dopamine-fl-hydroxylase from the adrenal gland that is stimulated by acetylcholine (11) suggests that exocytosis is the process by which norepinephrine release occurs. Because of the similarity of the ratios of norepinephrine to dopamine-,B-hydroxylase in tissue and in the amounts of norepinephrine and dopamine-,B-hydroxylase released (9,12), dopamine-,3-hyroxylase may be considered a reliable index of exocytosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, it has been shown that the overflow of dopainine-f3-hydroxylase, a vesicular protein which is released along with noradrenaline from nerve terminals (de Potter, de Schaepdryver, Moerman & Smith, 1969;Geffen, Livett & Rush, 1969), is also proportionally increased by phenoxybenzamine and by phentolamine in the saline-perfused spleen and vas deferens during nerve stimulation (de Potter, Chubb, Put & de Schaepdryver, 1971;Johnson, Thoa, Weinshilboum, Axelrod & Kopin, 1971).…”
mentioning
confidence: 99%